DEVELOPMENT OF A SELF-DIRECTION GAME HANDBOOK TO IMPROVE INHIBITORY CONTROL FOR 10–12-YEAR-OLDS - Sitaresmi, Dora; Kurniastuti, Irine (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Elementary school-age children need increased inhibitory control to focus and put aside things that are not priorities. Inhibitory control helps children to stay focused, control behavior, think before they act, and manage emotions. However, efforts specifically to increase the ability of inhibitory control have not been made much. This study aims to develop a guidebook to improve inhibitory control in children aged 10-12 years through the game "Self-Steering". This research is development research with the following steps: First, conducting a needs analysis through teacher interviews and classroom observations. Second, planning the manufacture of products as a solution to research problems. Third, making the product. Fourth, testing the product through expert validation and limited trials. Fifth, improving the product based on suggestions for improvement at the product trial stage. The result of this study is a game guidebook containing 3 inhibitory control games that were declared feasible by expert validators. Based on the field trial results, this game guidebook is an interesting game guide to improve children's inhibitory control. Some things that need to be improved will be discussed further.